Recent Progress in Polysaccharide Aerogels: Their Synthesis, Application, and Future Outlook - Muhammad, Arbanah (Polymers (Basel), 2021)
Porous polysaccharides have recently attracted attention due to their porosity, abundance, and excellent properties such as sustainability and biocompatibility, thereby resulting in their numerous applications. Recent years have seen a rise in the number of studies on the utilization of polysaccharides such as cellulose, chitosan, chitin, and starch as aerogels due to their unique performance for the fabrication of porous structures. The present review explores recent progress in porous polysaccharides, particularly cellulose and chitosan, including their synthesis, application, and future outlook. Since the synthetic process is an important aspect of aerogel formation, particularly during the drying step, the process is reviewed in some detail, and a comparison is drawn between the supercritical CO(2) and freeze drying processes in order to understand the aerogel formation of porous polysaccharides. Finally, the current applications of polysaccharide aerogels in drug delivery, wastewater, wound dressing, and air filtration are explored, and the limitations and outlook of the porous aerogels are discussed with respect to their future commercialization.